ANALISIS DAMPAK PERNIKAHAN DINI TERHADAP KEHIDUPAN KELUARGA DI DESA SUMBERKEDAWUNG KECAMATAN LECES KOTA PROBOLINGGO - Ahsandy Ramadhan Suardi; Fida, Imanuddin Abil (LPPM STAI Muhammadiyah Probolinggo, 2023)
Marriage at an early age has become a serious social concern in various societies. The purpose of this research is to evaluate the impact of early marriage on the dynamics of family life in that village. The research methodology involves surveys and structured interviews with several couples who got married at a young age. The research findings indicate that early marriage has complex effects on family life. While it can contribute to the formation of a strong family, early marriage also brings negative impacts such as family economic limitations, emotional immaturity of the partners, and higher health risks for both the mother and child. Factors such as education, employment, and social support play a key role in mitigating the negative impacts of early marriage. This study also proposes policy recommendations and intervention programs to enhance community understanding of the risks associated with early marriage and improve the quality of family life. Keyword : Early Marriage; Impacts of Early Marriage; Dynamics of Family Life